META ANALISIS: EFEKTIVITAS MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP PENINGKATAN KEMAMPUAN BERPIKIR KRITIS DALAM PELAJARAN PKN SD KELAS IV - Riski Sumaryanto; Naza Syawa Aulia; Auliya Tarisa Dwi Ngafiah (STKIP Subang, 2024)
This research aims to analyze previous relevant research that has been published in order to obtain a summary relating to the success of research on the Problem Based Learning learning model in improving critical thinking skills in Civics lessons in elementary schools. This research uses a meta-analysis method. The stages in meta analysis research are directing the topic, creating an overall design, collecting research samples, collecting data from the samples that have been collected, and analyzing the data obtained. The technique used by researchers in collecting data is by searching for articles in online journals that match the problem being studied. From the 12 articles that have been analyzed using the meta-analysis method in this research, it was concluded that the Problem Based learning model can improve critical thinking skills in Civics learning with the lowest average score being 3.33% and the highest average score being 3.33%. 69.25%, and an average increase of 31.55%.